Association between Cardiovascular Burden and Requirement of Intensive Care among Patients with Mild COVID-19 - Shi Tai; Jianjun Tang; Bilian Yu; Liang Tang; Yang Wang; Huilin Zhang; Weihong Zhu; Kui Xiao; Chuan Wen; Chongqin Tan; Zhongbiao Jiang; Chuanhao Jiang; et al. (Cardiovascular Therapeutics)
Background. Information regarding the impact of cardiovascular (CV) conditions on disease progression among patients with mild coronavirus disease 2019 (COVID-19) is limited. Methods. This study evaluated the association of underlying CV conditions with disease progression in patients with mild COVID-19. The primary outcome was the need to be transferred to the designated hospital for intensive care due to COVID-19 disease progression. The patients were divided into with and without CV conditions as well as stable and intensive care groups. Results. Of the 332 patients with mild COVID-19, the median age was 51 years (IQR, 40-59 years), and 200 (61.2%) were female. Of the 48 (14.5%) patients with CV conditions, 23 (47.9%) progressed to severe disease status and required intensive care. Compared with patients without CV conditions, patients with CV conditions were older and more likely to have fatigue, chest tightness, and myalgia. The rate of requiring intensive care was significantly higher among patients with CV conditions than in patients without CV conditions (47.92% vs. 12.4%; P<0.001). In subgroup analysis, the rate of requiring intensive care was also higher among patients with either hypertension or coronary heart disease (CHD) than in patients without hypertension or CHD. The multivariable regression model showed that CV condition served as an independent risk factor for intensive care (odds ratio (OR), 2.652 (95% CI, 1.019-6.899)) after adjustment for various cofounders. Conclusions. Patients with mild COVID-19 complicating CV conditions are susceptible to develop severe disease status and requirement for intensive care.